Migratory experience and heterogeneous times in contemporary Latin American testimony (Revista de Crítica Literaria Latinoamericana, 2016)
Criticism declares that there are risks to researchers’ homogenization of the ethnographic testimonies collected between the mid-20th century and the beginning of the 21st century. It is so, because, contrary to the first testimonies, those obtained in recent years show that the sociocultural gap between the informant and the amanuensis has become smaller, which has made the distinction between literate and illiterate more complex. However, these accounts, in particular those given by the migrant subjects (Cornejo Polar 1996), reveal the existence of a diversity of times and places, along with movables identities. That is, these testimonies emphasize a migratory condition that is heterogeneous.
Keywords: testimony; migrant subject; dichotomy; heterogeneity